(untitled) (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Frontoorbital advancement (FOA) was mainstay treatment of coronal and metopic craniosynostosis. There are several techniques and materials such as absorpable plate, surgical suture fixation, and osteogenesis distraction. Each techniques and materials has advantages to clinical outcome. This study describe our experience in FOA using surgical suture in our Institution.